Collapse and Continuity in the Kingdom of Aksum: Why the Stelae Fell but the Ark Endured - Belay Sitotaw Goshu (Polit Journal Scientific Journal of Politics, 2026)
The Kingdom of Aksum (c. 1st–7th centuries CE) stands as one of ancient Africa's most sophisticated civilizations, evidenced by monumental engineering feats including granite stelae weighing up to 500 tonnes. Yet by the 8th century, the centralized state had collapsed, its trade networks disintegrated, and its capacity for large-scale construction vanished. Paradoxically, the religious institutions that emerged alongside these monuments the Ethiopian Orthodox Tewahedo Church and its claim to house the Ark of the Covenant survived and became the enduring foundation of Ethiopian national identity for over 1,500 years. This paper addresses a central research Why did Aksum's political and technological systems collapse catastrophically while its spiritual systems demonstrated remarkable continuity? The study synthesizes archaeological evidence from the stelae field, paleoclimatic data from Lake Tana sediment cores, textual analysis of Ezana's trilingual inscriptions and the Kebra Nagast, and art historical examination of stele carving techniques and church architecture. Political and technological systems collapsed because they were fragile, centralized, and dependent on conditions that failed prolonged drought, trade disruption following Arab conquests, and soil exhaustion. Spiritual systems endured because they were decentralized, embedded in local communities, ritually reproducible without external inputs, and organized around portable or concealable symbols, particularly the Ark of the Covenant. Aksum's state exemplified a high-complexity, low-resilience system, while its religious institutions constituted lower complexity but higher resilience. Future research should pursue three directions: excavation of post-Aksumite rural settlements to understand local adaptation; paleoethnobotanical analysis of agricultural change during the drought period; and comparative study of religious resilience in other collapsed African states, including Great Zimbabwe and the Nubian kingdoms of Makuria and Alodia.